PELANGGARAN MAKSIM KUANTITAS DALAM PRINSIP KERJASAMA PADA KOMIK DETECTIVE CONAN VOLUME 65-67 KARYA AOYAMA GOSHO - Mahdalena, Liska Mahdalena; Isnaini, Zuli Laili Isnaini Laili; Basri, Merri Silvia Basri Silvia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Communication happens if only all participants understand and obey the cooperative principle in conversation. In facts, these principles are flouted for certain reason. The cooperative principle is consist of four maxims, those are quantity maxim, quality maxim, relevance maxim, and manner maxim. This research aims at finding out the type of flouting of quantity maxim in Detective Conan comic which volume  from 65 to 67 by Aoyama Gosho. Furthermore, this research tries to find the influence of flouting for success communication. The theory used in this study is the cooperative principle that introduced by Grice (1975). The research design applied in this study is a desrciptive qualitative research method  since the data are words and utterances instead. The data are 8 conversational fragments in Detetective Conan comic which flouting of quantity maxim. Based on Grice theory and also understanding on Leech’s explains about the flouting of maxim (1983), and finding the results are as follow: (1) has found 3 datas of flouting which strong-weak proposition, 2 datas which contain yes-no questions, 1 data which retisence, and 2 datas that utterances are more informative than is required (2) the flouting influence is not always cause the communication breakdown. In other words, in some cases, the  communication purpose become achievement even though maxims are flouted. Key Words: the flouting of quantity maxim, cooperative principle